WAYANG WINDU GEOTHERMAL RECHARGE AREA BASED ON FRACTURE ANALYSIS AND ASSOCIATED WITH WATER BALANCE AND GEOTHERMAL RESERVOIR SYSTEM - HENDRASTO (NIM : 32008003); pembimbing : Prof. Ir. Lambok M. Hutasoit, M.Sc., Ph.D; Prof. Dr. , FAJAR
Geothermal is known as a renewable energy resource and the renewing process occurs in the recharge area, where meteoric water enters a geothermal system. The InSAR technique application by using satellite image data of ALOS PALSAR and field verification using GPS geodetic measurement has been conducted to obtain earth surface model (DEM). Furthermore, the geological structure lineament also has been analyzed, and the result is fault and fracture density (FFD) map. The purpose of this research is to know meteoric water recharge area in detail and the percentage of meteoric water recharge by carrying out recharge calculation based on water balance, i.e. conducting rain fall - run off of tank model simulation by using NRECA and Sacramento models in the drainage river area (DRA) which is located in the elevation range of recharge area. Moreover, the hydrogeological modeling and fluid flow pattern are interpreted for the Wayang Windu geothermal system. Furthermore, to synthesize the relationship between the water balance calculation and the amount of meteoric water recharge for every FFD zone in each DRA and to determine whether a correlation exists between this recharge to the different types of geothermal reservoir system. The first hypothesis suggested in this research is that the geological structure in form of fracture at the earth surface in Wayang Windu area plays a role in meteoric water recharge based on water balance calculation result. The second hypothesis is that the amount of that recharge has a correlation to Wayang Windu geothermal reservoir system which has a different reservoir system, viz. vapor dominated reservoir in the northern part and water dominated reservoir in the southern part. The interpretation of FFD map and recharge area map resulting from stable isotope analysis shows that there are three high FFD zones interpreted as recharge areas for Wayang Windu geothermal reservoir. The recharge areas are situated in the northwestern part (Cisangkuy River), in the southwestern part (Cilaki River) and in the northeastern part (Citarum River) of Wayang Windu geothermal field. There is a significant correlation between fracture density in high FFD zone (unit in km/km2) and the result of field fracture density measurement (unit in m/m2). The fracture density value in high FFD zone, about 5 - 10 km/km2, could reflect the average density value of fracture, from the field measurement result, up to 7.9 m/m2. The lineament analysis from both methods show the same trend of geological lineament structure pattern, with lineament trend of northeast – southwest and southeast – northwest. viii The result of fracture characteristic analysis (intensity, density, aperture, fracture length) and the lithological type, shows that fracture tends to have increase rock permeability. The permeability in Cisangkuy DRA is interpreted higher than the other two DRA. The Cisangkuy DRA, located in igneous rock (andesite and basalt), has higher average fracture density value (about 5.3 m/m2) with value of fractal aperture is about -0,92 and -1,15 than in the other two DRA which are located in sedimentary rock (sandstone and claystone) have average density about 4.1 m/m2 with value of fractal aperture -1,94 for Cilaki DRA and about 3.1 m/m2 with value of fractal aperture -1,58 for Citarum DRA. To know the percentage of meteoric water infiltrated in that recharge area, infiltration analysis has been carried out based on water balance and synthetic discharge data for high FFD zone. The result of rain fall - run off simulation by using NRECA and Sacramento models is used to get empirical parameter or coefficient of infiltration value for each DRA. The correlation between discharge from the modeling and discharge from observation in the three DRA shows that Sacramento model is better compared with NRECA model. The ratio between the base flow discharge (as infiltration) and surface run off discharge by using Sacramento model is then conducted. The higher ratio percentage between the base flow discharge to the surface run off discharge, indicates that discharge that infiltrates into sub surface is higher than discharge which flows at the surface. The ratio shows that infiltration rate in the high FFD zone is higher than in the lower FFD zone. Related to fracture characteristic and lithology type, there is a different ratio percentage between base flow discharge and surface run off discharge in high FFD zone in each DRA. The ratio between base flow discharge to surface run off discharge in high FFD zone located in Cisangkuy DRA is higher (89%) than Cilaki DRA with ratio of 29%, and Citarum DRA, with ratio of 20%. It shows that the infiltration in the high FFD zone located in Cisangkuy DRA has higher infiltration rate compared with high FFD zone which is located in Cilaki DRA and Citarum DRA. These fracture planes are dominated by steep (vertical) dip. The geothermal reservoir type is influenced by the amount of water recharge. The recharge area in Citarum DRA is the nearest (about 3 km away) to vapor dominated geothermal reservoir (located in the north), but the percentage of meteoric water recharge is the smallest. On the other hand, Cilaki DRA and Cisangkuy DRA, which are located further (about 5 and 8 km) are capable of recharging more meteoric water into water dominated geothermal reservoir, which is located in the south.